The death and life of restaurants: A visualization in the eras of easy online ordering and increased metro mobility. (June 2019) - Zhou, Jiangping; Yang, Yuling
Like pubs in Western countries, restaurants in China are not just places where people consume drinks and eat food. They are also venues where acquaintances, friends, colleagues and families meet, relax, entertain, talk and socialize. In the era of fast-paced life, Fordism, easy online ordering and increased metro mobility, what could happen to restaurants in cities? To answer this, we collected and processed two distinct years (2014 and 2017) of point of interest and metro network data in Shenzhen, China. The visuals based on the data indicate that most metro station areas saw the advent of new restaurants as Shenzhen expanded its metro network, shortening the average travel time by transit between the two officially designated central business districts (CBDs): Luohu and Futian. Several metro station areas in or around the CBDs enjoyed the most growth in new restaurants. In terms of the 10 metro station areas that experienced the greatest decline in the number of restaurants, five of them were in areas that were around 15 minutes' metro travel from the CBDs. The remaining five scattered within suburbs rather than exurbs.